2019
DOI: 10.1002/cld.789
|View full text |Cite
|
Sign up to set email alerts
|

CON: Patients With Decompensated Cirrhosis Listed for Liver Transplantation Should Be Treated Posttransplant

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/14-1-reading-pedersen a video presentation of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Another retrospective, multicenter, Spanish study showed similar results: among 122 patients with decompensated cirrhosis without HCC receiving DAAs, 29 (24%) were removed from the transplant list due to clinical improvement [19]. Some reviews claim that patients with decompensated cirrhosis should be treated in the post transplant setting given that, when they are treated on the wait listing, there is a decreased SVR12 rate, the clinical improvement is not enough to remove many patients from the transplant list and there are serious safety concerns, including rapid deterioration and death [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective, multicenter, Spanish study showed similar results: among 122 patients with decompensated cirrhosis without HCC receiving DAAs, 29 (24%) were removed from the transplant list due to clinical improvement [19]. Some reviews claim that patients with decompensated cirrhosis should be treated in the post transplant setting given that, when they are treated on the wait listing, there is a decreased SVR12 rate, the clinical improvement is not enough to remove many patients from the transplant list and there are serious safety concerns, including rapid deterioration and death [20].…”
Section: Discussionmentioning
confidence: 99%